Studi Kandungan Mikroplastik pada Kerang Lorjuk (Solen Sp.) di Perairan Dusun Pesisir, Desa Kaduara Timur, Kabupaten Sumenep, Jawa Timur - Nuril Nabila Al Hidayah (Program Studi Ilmu Kelautan, FIPAK, Universitas OSO, 2025)
Microplastics are very small fragments, which are less than 5 mm, the result of degradation of plastic waste. Solen sp. or lorjuk clams are included in the Solenidae family, which is a type of filter feeder animal or filters the surrounding water to get food so it is very likely that microplastics will also be eaten. The research location is located in Pesisir Hamlet, East Kaduara Village, Sumenep Regency where local residents still dispose of garbage into the sea. The purpose of this study was to analyze the concentration and characteristics of microplastics in Solen sp., as well as the relationship between length and weight of Solen sp. on the amount of microplastics. Sampling was carried out by random sampling method and obtained a total sample of 138 samples and divided into 3 classes based on the length of the shell. Class 1 shell length was 2.80 – 3.14 cm for 22 samples, class 2 was 3.15 – 3.54 cm for 78 samples, and class 3 was 3.55 – 4.00 cm for 38 samples. The average value of microplastic concentration in Solen sp. that is equal to 23.81 items/g in class 1, in class 2 that is 13.26 items/g, while in class 3 that is 7.11 items/g. The microplastic content found in lorjuk shells or Solen sp. 328 particles were found in the form of fragments, 251 particles in the form of pellets, 405 particles in the form of fibers, and 293 particles in the form of films. The colors of the microplastics found were black, blue, yellow, red, purple, green, white and transparent. Shell length and Solen sp weight have a very weak correlation to the amount of microplastics.